Effectiveness of video self-instruction training on cardiopulmonary resuscitation retention of knowledge and skills among nurses in north-western Nigeria - Saidu, Ahmed; Lee, Khuan; Ismail, Iskasymar; Arulogun, Oyedunni; Lim, Poh Ying (Frontiers in Public Health, 2023)
Background: Adaptable cardiopulmonary resuscitation/basic life support (CPR/BLS) training are required to reduce cardiac arrest mortality globally, especially among nurses. Thus, this study aims to compared CPR knowledge and skills retention level between instructor-led (control group) and video self-instruction training (intervention group) among nurses in northwestern Nigeria. Methods: A two-arm randomized controlled trial study using double blinding method was conducted with 150 nurses from two referral hospitals. Stratified simple random method was used to choose eligible nurses. For video self-instruction training (intervention group), participants learnt the CPR training via computer in a simulation lab for seven days, in their own available time whereas for instructor-led training (control group), a one-day program was conducted by AHA certified instructors. A generalized estimated equation model was used for statistical analysis. Results: Generalized Estimated Equation showed that there were no significant differences between the intervention group (p=.055) and control group (p=.121) for both CPR knowledge and skills levels respectively, whereas higher probability of having good knowledge and skills in a post-test, month and three-month follow-up compared to baseline respectively, adjusted with covariates (p<.05). Participants had a lower probability of having good skills at six-month follow-up compared to baseline, adjusted with covariates (p=.003). Conclusion: This study showed no significant differences between the two training methods, hence video self-instruction training is suggested can train more nurses in a less cost-effective manner to maximize resource utilization and quality nursing care. It is suggested to be used to improve knowledge and skills among nurses to ensure cardiac arrest patients receive excellent resuscitation care.